The Usefulness of Digital Tomosynthesis (DT) in Assisting in Cases of Doubtful Routine Radiography and/or Computed Tomography (CT) Image. - Suchato, Chirotchana (The Bangkok Medical Journal, 2015)
Digital tomosynthesis is useful in assisting the detection of diseases in many medical fields. For example it demonstrates in the chest in the early detection of lung cancer, in the musculoskeletal system in trauma, in osteolysis for hip prosthesis and in arthritis, urolithiasis in the urologic system and so on. This article excludes digital breast tomosynthesis because this is well established elsewhere.